Time Series for Evaluation of Performance Metrics as of Interaction with an AR-Sandbox Using Brain Computer Interfaces - Restrepo Rodríguez, Andrés Ovidio; Ariza Riaño, Maddyzeth; Gaona-García, Paulo Alonso; Montenegro-Marín, Carlos (Lecture Notes in Networks and Systems, 2023)
Technologies such as Augmented Reality (AR) can generate an impact within the educational process of students, which can be measured from the perspective of users. Generally, this perspective is evaluated from questionnaires that may lack objectivity and veracity. An alternative is the use of brain-computer interfaces that allow users to capture brain activity while interacting with the environment. The purpose of this study is to evaluate the perspective of a group of children when interacting with an AR-Sandbox, defining scenarios for the practice of vowels and geometric figures with the sand. This is achieved by performing a trend analysis of the time series identified from the capture of performance metrics using the Emotiv EPOC device. The results of this study show in the group of participants an average increasing trend of 60% in their interest, engagement, focus, relaxation and stress when interacting with the immersive environment.
Keywords: AR-Sandbox; augmented reality in education; brain computer interface (BCI); information technologies in education; performance metrics; time series analysis; user perspective; Scopus(2)